Keberhasilan UNDP melalui Program HPMP dalam Pembentukan Kebijakan Perlindungan Lapisan Ozon di Indonesia - Meidiana Farhani; Novita Putri Rudiany (Universitas Diponegoro, 2020)
This article analyzes the role of the United Nations Development Program (UNDP) through the Hydrochlorofluorocarbons Phase-Out Management Plan (HPMP) Program which encourage Indonesia to implement regulations at the ministerial level that aim to undertake ozone layer protection and the phasing-out of the substances that deplete the ozone layer in Indonesia. This shows the role of international organization to shape national regulation in member states. In analyzing these problems, researchers used the framework of the international norm diffusion, specifically the conditions on economic assistance and the interaction with transnational actors, also the State Socialization. This study uses qualitative methods that emphasize non-numeric data and by conducting studies in previous studies. The conclusion of this research is that the UNDP through the HPMP Program has played a role in establishing national regulations related to Ozone Layer Protection and the phasing out of the substances that deplete the ozone layer which is regulated in Minister of Industry Regulation Number: 41/M-Ind/Per/5/2014 and Regulation of the Minister of Trade Number: 55/M-Dag/Per/ 9/2014.